Amazonian medicinal plants used in the treatment of digestive system disorders: a literature review (Research, Society and Development, 2021)
The digestive system is made up of several organs and their annexes, whose function is to process food and absorb nutrients, allowing the body to function properly. Therefore, the search for knowledge and improvement of the therapeutic actions of these medicinal plants, following scientific bases, comes with the purpose of obtaining and propagating information about these plants and their pharmacological actions against the symptoms of diseases of the digestive system. The present work had as objective a bibliographic review about the use of Amazonian medicinal plants in the treatment of digestive system disorders, through SciELO - Scientific Electronic Library Online and PubMed - National Library of Medicine databases. From August to October, 25 scientific articles were screened between the years 2017 to 2021, as exclusion criteria, species that were not from the Amazon region, that did not correspond to the research objective or topic addressed and that did not were used. Contemplate the selected time period. For the result of this research, after applying the exclusion criteria, 14 articles referring to plant species were selected, which contained all the necessary information such as: scientific and popular name, used part, preparation method, chemical composition, therapeutic action and contraindications that they proposed to obtain knowledge at a scientific and popular level, and the importance of the role of the pharmacist in relation to their knowledge of medicinal plants. In this way, it is possible to systematize knowledge about the correct and rational use of herbal medicine on the proposed topic. Frames of information on the topic were created to provide the reader with greater engagement in the topic and, in this way, it is possible to organize in a more practical and direct way the knowledge about the use of these plants in the Amazon region for the treatment of some digestive disorders. The theme proved to be of relevance given the wealth of traditional knowledge added to practice, which in this way systematically contributes to the safety and rational use of herbal medicine in the region.